Development of a vesicular stomatitis virus pseudotyped with herpes B virus glycoproteins and its application in a neutralizing antibody detection assay - Kinoshita, Hitomi; Yamada, Souichi; Ogawa, Takuma; Nguyen, Phu Hoang Anh; Harada, Shizuko; Kawahara, Madoka; Ishijima, Keita; Maeda, Ken; Ebihara, Hideki; Fukushi, Shuetsu (mBio, 2024)
Herpes B virus (BV) is a highly pathogenic zoonotic virus against humans. BV belongs to the genus Simplexvius , the same genus as human herpes simplex virus (HSV). By contrast to HSV, cell entry mechanisms of BV are not fully understood. The research procedures to manipulate infectious BV should be conducted in biosafety level (BSL)-4 facilities. As pseudotyped viruses provide a safe viral entry model because of their inability to produce infectious progeny virus, we tried to generate a pseudotyped vesicular stomatitis virus bearing BV glycoproteins (VSV/BVpv) by modification of expression constructs of BV glycoproteins, and successfully obtained VSV/BVpv with a high titer. This study has provided novel information for constructing VSV/BVpv and its usefulness to study BV infection.